2020
DOI: 10.1002/bkcs.12159
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Recognition Features of a Naphthobipyrrole‐strapped Calix[4]pyrrole

Abstract: A calix[4]pyrrole (1) strapped with a naphthobipyrrole was prepared and its ability to bind the bicarbonate anion (HCO3−) was investigated via 1H NMR and UV/Vis spectroscopic analyses. The resulting spectral data revealed that receptor 1 was capable of recognizing HCO3− with high affinity in solutions as well as in the solid state. In CD2Cl2, it was inferred from 1H NMR spectroscopic titration experiment that HCO3− interacts with receptor 1 via two different modes with the first involving HCO3− being hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…To verify the detection principle of Probe 1 to H 2 S, the expected product 4 was analyzed by using 1 H NMR and ESI‐MS 19 . After reaction with H 2 S in aqueous solution, Probe 1 was anticipated to be disappeared and a new compound 4 would appear predominantly (Figure 6a).…”
Section: Methodsmentioning
confidence: 99%
“…To verify the detection principle of Probe 1 to H 2 S, the expected product 4 was analyzed by using 1 H NMR and ESI‐MS 19 . After reaction with H 2 S in aqueous solution, Probe 1 was anticipated to be disappeared and a new compound 4 would appear predominantly (Figure 6a).…”
Section: Methodsmentioning
confidence: 99%
“…4), exhibiting comparatively higher binding affinity towards HCO 3 − ( K a = 1170 M −1 ) than the simple C4P in both the solid-state and solution phases, as revealed by the UV-Vis and 1 H-NMR spectroscopic titrations. 82 The relatively superior binding affinity with HCO 3 − is ascribed to the extra NH-hydrogen bonding interactions of the strap with HCO 3 − in addition to the usual preliminary NH-bonding contacts of the C4P scaffold. Fascinatingly, the 1 H-NMR studies carried out in CD 2 Cl 2 revealed two binding modes of receptor ( 35 ) with HCO 3 − .…”
Section: Functional C4ps As Versatile Receptorsmentioning
confidence: 99%
“…4), exhibiting comparatively higher binding affinity towards HCO 3 − (K a = 1170 M −1 ) than the simple C4P in both the solid-state and solution phases, as revealed by the UV-Vis and 1 H-NMR spectroscopic titrations. 82 The relatively NH-hydrogen atoms through H-bonding, leading to the generation of an anion-receptor complex (36 − ) (Fig. 4).…”
mentioning
confidence: 99%
“…[15][16][17][18][19] By contrast, the number and the acidity of the hydrogen bond donors belonging to the receptor would dictate the anion affinity of the receptor. [20][21][22][23][24][25][26] In general, an anion receptor possessing larger number of hydrogen bond donors and more acidic hydrogen atoms recognize anions with higher affinity via the formation of relatively strong hydrogen bonds. [15][16][17][18][19][20][21][22][23][24][25][26] The acidity of an anion receptor can be enhanced by introducing an electron-withdrawing group into its anion binding motifs bearing hydrogen bond donors.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] In general, an anion receptor possessing larger number of hydrogen bond donors and more acidic hydrogen atoms recognize anions with higher affinity via the formation of relatively strong hydrogen bonds. [15][16][17][18][19][20][21][22][23][24][25][26] The acidity of an anion receptor can be enhanced by introducing an electron-withdrawing group into its anion binding motifs bearing hydrogen bond donors. [24][25][26][27] The receptor geometry also plays a role in determining the binding strength and selectivity of the receptor for anions in question.…”
Section: Introductionmentioning
confidence: 99%